CORRUPTION POTENCIES IN LAND USE POLICY (A Case Study in Kuningan Regency) - Haris Budiman; Eman Suparman; Anis Mashdurohatun (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The occurrence of land use at a policy area in the field of land use causes some law problems. It relates to the licensing mechanism that has not been optimal yet. As the result of the policy is that society suffers loss due to inconsistent policy. The problems of this research are how the implementation of a policy in the field of land use is, what factors are causing the policy that led to the change of land use, and whether or not a policy that harms society can be classified in to a corruption act. This research is normative legal research and the approach used is qualitative.The potency of corruption can occur when there are the growth and development actions especially relating to the economy that has been running fast, and cause various changes. Local government’s policy in the field of land use by giving loose and ease in licensing is an activity which potentially causes corruption. Keywords : policy, land use, corruption potency